Fish otoliths from the Paleocene (Selandian) of West Greenland - Schwarzhans, Werner (Meddelelser om Grønland. Geoscience, 2004)
Fish otoliths are described from the Middle Paleocene from Nuussuaq in central West Greenland. A total of 24 species is described, 7 as newly established and 4in open nomenclature. All specimens were obtained from the Sonja lens of the Agatdal Formation (Selandian) in the central part of the Nuussuaq peninsula. This is the first record of fossil otoliths from Greenland. The faunal association is interpreted as shallow shelf, near shore neritic but nevertheless shows a high degree of similarity with time equivalent otolith based teleost faunas from deeper environments from the U.S. Gulf coast and Europe (Denmark), the latter having been recently reviewed and described by Schwarzhans, 2003. 7 new species are introduced and described. The new taxa are: Neoscopelus nuussuaqensis, genus ?Percopsiformorum resonus, Palaeomorrhua thulei, genus Veliferidarumgroenlandicus, Hoplostethus durus, genus Berycidarum tener, genus Acropomatidarum rosenkrantzi.